Yaqui Delgado wants to kick your ass - Medina, Meg 1963- (Candlewick Press, 2013)
"One morning before school, some girl tells Piddy Sanchez that Yaqui Delgado hates her and wants to kick her ass. Piddy doesn't even know who Yaqui is, never mind what she's done to piss her off. Word is that Yaqui thinks Piddy is stuck-up, shakes her stuff when she walks, and isn't Latin enough with her white skin, good grades, and no accent. And Yaqui isn't kidding around, so Piddy better watch her back. At first Piddy is more concerned with trying to find out more about the father she's never met and how to balance honors courses with her weekend job at the neighborhood hair salon. But as the harassment escalates, avoiding Yaqui and her gang starts to take over Piddy's life. Is there any way for Piddy to survive without closing herself off or running away?"...Publisher's web site